Impact of Extracurricular and Cocurricular Science Activities on Students’ Scientific Creativity: A Quasi-Experimental Study - Lamsal, Umanath (ILAM इलम, 2026)
This quasi-experimental study aims to assess effectiveness of structured extracurricular and cocurricular activity program on the scientific creativity of Grade IX students in Nepal. In this study, 136 participants were selected from two secondary schools in Kathmandu Valley who were divided into experimental (n = 70; boys = 30, girls = 40), and control (n = 66; boys = 42, girls = 24) groups. The experimental group took part in an 8-month intervention using ECA/CCA programs. To assess the scientific creativity, Scientific Creativity Test (SCT) developed by Hu and Adey (2002) was used. The data was analyzed through descriptive statistics, independent samples t-tests, and Cohen's d effect size. The results demonstrated that students in the experimental group showed statistically significant progress in scientific creativity in comparison to the control group [t(134) = 4.32, p < .001, Cohen's d = 0.74] which produced a medium-to-large effect size. Similarly, there is no gender-based differences visible between pre- and post-intervention during the study as the p-values of the t-tests were found above 0.05. The study demonstrates that ECA/CCA programs which educational institutions design to meet their particular needs functions as effective educational methods for developing scientific creativity in Nepal's resource-limited educational settings which extends to all areas of curriculum development and teacher education and inclusive science education policy creation.